Combination IETA Ultrasonographic Characteristics Simple Scoring Method With Tumor Biomarkers Effectively Improves the Differentiation Ability of Benign and Malignant Lesions in Endometrium and Uterine Cavity - Lin, Dongmei; Zhao, Liang; Zhu, Yunxiao; Huang, Yujun; Yuan, Kun; Liu, Wenfen; Li, Shengli; Guo, Xia; Hao, Yi (Frontiers in Oncology, 2021)
Objectives To evaluate IETA ultrasonographic characteristics simple scoring method and tumor markers for the diagnosis of endometrial lesions. Methods We classified and scored the normalized description of IETA ultrasonic characteristics, according to IETA expert consensus literatures, previous IETA related research articles and the previous research experience of this project group. We conducted a retrospective analysis of the ultrasound images of 594 patients enrolled. Meanwhile, the results of seven tumor markers were combined. The diagnostic efficiency between the combined method and the single method for benign and malignant uterine cavity or endometrial lesions were compared. Results 594 cases were confirmed by postoperative pathology or surgery records, including 475 benign lesions and 119 malignant lesions. In the simple ultrasound scoring method, the average score of benign lesions was 3.879±1.279 and that of malignant lesions was 9.676±4.491. If≥6.5 points was taken as the cut-off value for the judgment of malignant lesions, the sensitivity, specificity, coincidence rate and the area under ROC curve (AUC) were 76.5%, 96.0%, 94.4%, and 0.935, respectively. The difference of Ca19-9 and HE4 between benign and malignant lesions was statistically significant (all P≤0.01). The other five tumor markers (Ca125, CA15-3, SCC-Ag, AFP and CEA ) were showed no statistically significant difference in benign and malignant lesions. If the value of Ca19-9 ≥13.96 U/ mL was taken as cut-off value, the sensitivity, specificity and coincidence rate were 54.6%, 74.7%, 73.3%, respectively, and the AUC was 0.620. If the value of HE4 ≥ 39.075 pmol/L was taken as cut-off point, the sensitivity, specificity, coincidence rate and AUC were 77.3%, 67.9%, 68.6% and 0.796, respectively. The sensitivity was increased to 96.6% and the AUC was 0.937, when IETA ultrasound characteristics simple scoring method combined Ca19-9 and HE4 in parallel test. Conclusions In IETA ultrasound characteristics simple scoring method, with≥6.5 points as the cut-off value, it could quickly and accurately assess the benign and malignant in uterine cavity and endometrial lesions, with high diagnostic value. The diagnostic efficacy of seven tumor markers was all mediocre. Combining with these two methods, the comprehensive diagnosis could improve sensitivity and accuracy, reduce the risk of missed diagnosis.